Effect of Collector Roughness on Properties of Amorphous Silicon Thin‐Film Anodes. Issue 12 (24th May 2019) - Xue, Wendong; Tian, Xu; Xue, Yawen; Peng, Ting; Li, Yan; Li, Yong; Sun, Jialin
Abstract: Uniform silicon films about 500 nm thick for lithium‐ion batteries on copper foil current collectors were prepared using a magnetron sputtering method. We discuss the surface morphology and crystal structure of the silicon films, emphasizing how the current collector affects the performance of the silicon film anode. XRD and Raman analysis demonstrate that both films are amorphous. However, the silicon film deposited onto the matte copper foil shows better cycle behavior, it can be discharged at 0.5 C with 84.1 % capacity retention about 1470 mAhg −1 after 100 cycles. Abstract : Find relief : An amorphous silicon film about 500 nm is fabricated by using a magnetron sputtering method. This amorphous silicon film anode relieves the huge volume expansion during the lithiation‐delithiation process and exhibits a high capacity as well as good cycling performance.